Heterogeneous nuclear ribonucleoprotein A1 post-transcriptionally regulates Drp1 expression in neuroblastoma cells - Park, So Jung (Biochim Biophys Acta, 2015)
Excessive mitochondrial fission is associated with the pathogenesis of neurodegenerative diseases. Dynamin-related protein 1 (Drp1) possesses specific fission activity in the mitochondria and peroxisomes. Various post-translational modifications of Drp1 are known to modulate complex mitochondrial dynamics. However, the post-transcriptional regulation of Drp1 remains poorly understood. Here, we show that the heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) regulates Drp1 expression at the post-transcriptional level. hnRNP A1 directly interacts with Drp1 mRNA at its 3′UTR region, and enhances translation potential without affecting mRNA stability. Down-regulation of hnRNP A1 induces mitochondrial elongation by reducing Drp1 expression. Moreover, depletion of hnRNP A1 suppresses 3-NP-mediated mitochondrial fission and dysfunction. In contrast, over-expression of hnRNP A1 promotes mitochondrial fragmentation by increasing Drp1 expression. Additionally, hnRNP A1 significantly exacerbates 3-NP-induced mitochondrial dysfunction and cell death in neuroblastoma cells. Interestingly, treatment with 3-NP induces subcellular translocation of hnRNP A1 from the nucleus to the cytoplasm, which accelerates the increase in Drp1 expression in hnRNP A1 over-expressing cells. Collectively, our findings suggest that hnRNP A1 controls mitochondrial dynamics by post-transcriptional regulation of Drp1.